ANALISIS PUISI BERJUDUL DENYUT NADI KARYA ACHLUDDIN IBNU ROCHIM:: Struktur Kebatinan, Sosial, Dan Simbolisme Dalam Kritik Sosial-Poetik - Hayuning Jagatnira Bentang Pakerti, Andia (TANDA: Jurnal Kajian Budaya, Bahasa dan Sastra (e-ISSN: 2797-0477), 2023)
The poem Denyut Nadi (Pulse) by Achluddin Ibnu Rochim represents the collective sentiment of a society burdened by social, economic, and political crises. Through natural metaphors, the poet’s inner state is articulated in a poetic and reflective rhythm of protest. This study aims to uncover the spiritual structure, social symbols, and critique of power embedded within the poem’s structure. By employing a structural and semiotic approach, this research reveals that the poem serves as a medium of expression for the anxiety surrounding democratic stagnation and the suffering of the people.